Physical-chemical characteristics determination of potato (Solanum phureja Juz. and Bukasov) starch (2017)
The aim of this research was to evaluate the functional properties of the native potato (Solanum phureja Juz. and Bukasov) starch in the food and non-food industry for which a thermal analysis was conducted, including thermogravimetric (TGA) analysis, differential scanning calorimetry (DSC) analysis, X-ray diffraction (XRD) analysis, morphologic analysis via scanning electron microscopy (SEM), and rapid viscoamylograph analysis (RVA). The RVA analysis showed that gelatinization temperature was 63.95 °C, the maximum viscosity was 1087 cP and ease of cooking was 7 min. The thermogravimetric (TGA) analysis revealed three stages: in the first, the product had weight loss of 9.51%; in the second, a weight loss of 53.88%; and in the third, a weight loss of 37.91%. The differential scanning calorimetry (DSC) analysis found that heat flux initiates at 50.97 °C, where the starch gelatinization transition starts, ending at 71.25 °C with enthalpy of 2.11 J.g-1. Evaluation of the native potato starch demonstrated that this product is an excellent alternative in the elaboration of different products which need a thickener in cooking processes, given that its behavior at high temperatures, which have allowed to maintain its structure.